A JAVANESE PANJI ROMANCE: ANALISIS STRUKTUR CERITA PANJI PADA NASKAH WANGBANG WIDAYA - Fitrotul Hikmah; Roihanah Roihanah (LP3M IAI Al-Qolam, 2017)
Panji's story is a classic romance originating from East Java. One variant of Panji's story is Wangbang Widèya: A Javanese Panji Romance. Research on this manuscript is rarely done, or there is research on the same topic, but different theoretical basis as a tool for study. The purpose of this study is to indirectly examine the literary aspect that possible further research coupled with intrinsic research. Research focuses on studying intrinsic aspects that include: theme, plot, character and characterization, and background story. This research is library study using qualitative research method. The source of this research data is Wangbang Widèya: A Javanese Panji Romance. This process begins with data collection in the form of primary and secondary data. The analysis comprises data reduction, data classification, and data display. In the final process of data display, it has presented data ready to be analyzed. The results show: (1) the theme of romance is an absolute theme in Wangbang Widèya: A Javanese Panji Romance; (2) the groove is loose because it is easily inserted with other stories that complement the story as a whole; (3) the characters and the characterizations are static, namely if the character is good then he will get the victory, but if the character is evil it will get defeated; (3) the settings in Wangbang Widèya: A Javanese Panji Romance cover the setting of place, time, atmosphere, and social aspect as the explanation of the character strata. Keywords: the structure of the story, manuscript, Wangbang Widèya: A Javanese Panji Romance